Riqueza e redundância utilitária da assembléia de plantas e animais forrageados para fins medicinais no semiárido do nordeste brasileiro - NASCIMENTO, André Luiz Borba do (2013)
Plants and animals are used as important medicinal resources by rural communities worldwide. Its uses can result in impact to biodiversity. However studies that seek to understand the interaction between these two resources in the same local medical system are nonexistent. An important tool for this type of research is the utilitarian redundancy model, because it allows us to evaluate how the richness of medicinal resources is distributed among the different therapeutic targets, indicating possible overlapping of use between plants and animals and revealing species that could suffer a higher use pressure. This model also involves issues related to resilience, predicting that therapeutic targets with a smaller arsenal of species would be more vulnerable to changes in local medical systems. In this context, this study aims to investigate the relationships between the use of medicinal plants and animals and the traditional medical system of Horizonte, which is an extractive community located in the Environmental Protection Area of FLONA Araripe - Apodi in the semiarid region of Northeastern Brazil. We found that most of the therapeutic targets treated by animal substances are overlapped, i.e., are also treated by plant substances, and these targets concentrate most of medicinal resources. They are perceived as very usual, although considered a little dangerous. This similar behavior of people using medicinal plants and animals reflect in the formation of a common core of knowledge, shared by most of the community. Furthermore, the population considers plants and animals equally effective in curing overlapped therapeutic targets. However, plants are used mostly due to their greater availability. The data also indicates that women have more knowledge about medicinal resources closer to their residential area; a space where they spend more time due to their responsibilities in taking care of the families. On the other hand men know more about medicinal resources related to forests; spaces often more visited by them. This occur because they are responsible for supporting their families, fact that leads them to frequently explore these areas. The results indicate the existence of general patterns related to the use of medicinal resources, in which the energy optimization, perceived priorities, spaces occupied and social functions seem to guide the use, collection and the sharing of knowledge of medicinal plants and animals; attributing greater resilience and adaptability to the local medical system.